Sanitasi Pemukiman Bantaran Sungai Deli Dalam Konstruksi Sosial Budaya Kelurahan Bahari Medan Belawan Kota Medan - Sri Widari Zulfa; Hidayat Amsani; Fikarwin Zuska (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This paper aims to determine the sanitation and health conditions of the people on the banks of the Deli river which are constructed socially and culturally. The problem is focused on community participation in treating household waste, using toilets, and obtaining clean water sources and their relationship to public health. Data were collected based on an ethnographic approach, namely through observation and in-depth interviews which were analyzed qualitatively. The results of this study are the residents of the riverbanks of Deli who live in illegal settlements, carry out activities such as toilets in the river and at the same time use the river as a place for household waste disposal. Activities aimed at maintaining personal hygiene and health are carried out in rivers as well as places for disposing of sewage and household waste. The activity of using rivers as a place to dispose of human and household waste is one of the factors of poor sanitation that affects health status. This study concludes that the sanitary conditions in the residential banks of the Deli River are caused by economic and knowledge factors. Improving the riverbank sanitation system requires collaboration between the community, government and health educators.